Examining the relationship between learning organization characteristics and change adaptation, innovation, and organizational performance - Kontoghiorghes, Constantine; Awbrey, Susan M.; Feurig, Pamela L. (My University, 2005)
The main purpose of this exploratory study was to examine the relationship between certain learning organization characteristics and change adaptation, innovation, and bottom-line organizational performance. The following learning organization characteristics were found to be the strongest predictors of rapid change adaptation, quick product or service introduction, and bottom-line organizational performance: open communications and information sharing; risk taking and new idea promotion; and information, facts, time, and resource availability to perform one's job in a professional manner.